Analisis Incremental Capital Output Ratio (ICOR) Kota Semarang - Muhamad Yamani (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2022)
Investment is one of the most important and vital variables in the economic activities of every country. The Incremental Capital Output Ratio (ICOR) is the ratio of investment to GDP which is one of the macro indicators of the efficiency level of an economy. The investment value of Semarang City has a large contribution to investment in Central Java. This makes the level of investment efficiency in the city of Semarang very important. The method of analysis in this study is descriptive analysis, which describes the results of table and graph analysis. While the ICOR calculation method uses the standard ICOR method. The data used are secondary data obtained from BPS Semarang City, including GRDP data by business field and GRDP data by expenditure. The results showed that investment activities carried out in Semarang City during the 2015-2019 period were relatively less efficient or economic activities that developed in Semarang City tended to be capital intensive, even more inefficient than Central Java.